Days of August [videorecording (DVD)] - Sepulveda, Santiago; MacAllan, Teryn; Gould, Logan; McCarthy, Thomas (Filmhub, 2025)
"In a dystopian America dominated by a tyrannical police state, forbidden romance and a movement to resist the government stir in the city of Harpswell."--